Total Organic Carbon and Total Nitrogen Contents in Lake Sediment as a Proxies of Paleoclimate - 公文, 富士夫
湖沼堆積物中の全有機炭素(TOC) ･全窒素(TN)含有率に関連する最近の研究を概観した.TOCおよびTNには,湖水中で自生するものと,陸上から運び込まれる外来性のものがあり,通常の調和型湖沼では前者を起源とするものが優占する.木崎湖における最近の研究では, 1983年から1999年にかけての湖底堆積物中のTOC含有率は,同じ期間の湖水中の年間クロロフィルa量および冬の平均気温(12月～翌3月の平均)との問によい相関があることが認められた.このことは,気温が湖水中の生物生産性に彩響を与えることを通じて,湖沼堆積物中への有機物流入を支配していることを意味する.野尻湖底堆積物のコア試料中のTOCとTNの含有率およびC/Nの変動を過去4.5万年間にわたって解析したところ,クリーンランドの氷床コアにおける酸素同位体変動が示す寒暖変動とよく一致する結果を得た.野尻湖の堆積物コアについての最近の研究では, TOCやTNの増減が気候に支配された花粉組成の変化と対応することも示されている.これらの事実は,湖沼堆積物中のTOCやTNの含有率が,気候変動の指標として有効であることを示している. Recent researches on total organic carbon(TOC) and total nitrogen (TN) contents in lake sediment are overviewed. TOC and TN originate from autochthonous organic products in the lake and external products derived from the land area the former are dominant in oligotrophic lakes. It has been recognized recently that the TOC content in modern sediments from AD 1983 to 1999 has a good relationship with annual chlorophyl a amounts and average winter temperatures (from December to March) in Lake Kizaki. This result means that temperature controls the TOC content and also flux in sediment via productivity in lake water. The TOC, TN, and C/N amounts measured in a sediment core from Lake Nojiri show an excellent example of climate variability during the past 45ka, which may correspond well with δ¹⁸O change revealed in the ice core (GRIP) from Greenland. The study of lake sediments in Lake Nojiri also confirmed that the sequential changes of TOC and TN contents correspond well with the changes in pollen composition controlled by climate. These facts suggest that contents of TOC and TN, and C/N ratio in lake sediment may be a powerful tool to clarify climate change. Article 第四紀研究. 42(3):195-204 (2003) journal article